Development of herbed kesong puti from carabao's milk - Castillo, Eileen Antonio
ABSTRACT An attempt was made to manufacture a new variety of the traditional kesong puti from carabao's milk through addition of basil and garlic herbs. The study was carried out in three phases. Six lots of cheese were produced in Phase I with different basil and garlic ratios. Sensory evaluation was performed, the ANOVA and DMRT results showed that 80% basil and 20% garlic was the most preferred ratio. This ratio was employed for the determination of the most acceptable amount of spice in the kesong puti in phase II. Three lots of herbed kesong puti were made and added with varying concentration of spice. Sensory evaluation showed no difference in overall acceptability, appearance, saltiness, basil flavor, garlic flavor and texture/mouthfeel. There was, however, significant difference in terms of herb content and herb content acceptability with a higher preference for the product that was prepared with 10% basil-garlic mixture in the cheese formulation. Verification studies revealed that kesong puti made with 10% basil-garlic mixture in the cheese formulation has consumer acceptability ratings between "like moderately" and "like very much". The herbed kesong puti was characterized by green and yellowish specks of basil and garlic on its surface and body which made the cheese appear unusual from the traditional white kesong puti. This was, nevertheless, appreciated by the panelists indicating that another variety of kesong puti from carabao's milk with color different from that of the traditional kesong puti would be welcome. Kesong puti characterized by finely chopped basil leaves and granulated garlic mixed in the curd was developed to add to the varieties of kesong puti from carabao's milk thus exploring further the countess possibilities of this indigenous product. The study was conducted in three phases. Phase I involved the determination of the most acceptable ratio basil and garlic herb in the soft cheese. 80% basil and 20% garlic proved to be the most acceptable ratio. In phase II, the most acceptable amount of herbs, was determined through sensory evaluation of three samples with varying spice concentration. The sample with 10% spice proved to be the most acceptable amount of spice. The result from phase I and II was used in the consumer acceptability test in Phase III and the finished product was liked between moderately to very much.